A Guidance Strategy for Strapdown Seeker considering Minimum Field-of-View Angle Constraint - Guanqun Zhou; Qunli Xia (International Journal of Aerospace Engineering)
An off-axis strapdown seeker in missile may lead to a minimum field-of-view (FOV) angle constraint problem. The goal of this paper is to deal with the problem in guidance. Analysis of kinematics proves that on the premise of attacking stationary target, seeker look angle comes to 0 before or at the end time, and seeker will lose target finally. In order to reduce the distance of seeker losing target, a guidance strategy is proposed to sustain minimum FOV angle constraint during flight. The strategy can be applied on guidance laws with independent orders in longitudinal and lateral channels. By means of a certain rolling maneuver, it keeps the target in the seeker’s limited FOV. Moreover, a lateral guidance order compensation is utilized in the strategy to maintain seeker look angle. Simulations and comparisons are conducted to demonstrate the strategy’s effectiveness. Results show that the guidance strategy can sustain minimum FOV angle constraint longer than classical guidance method.